Hubungan Antara Konsumsi Karbohidrat Dan Kolesterol Terhadap Kadar Glukosa Darah Pada Penderita Diabetes Melitus Tipe Ii Rawat Jalan Di Rsud Dr.Moewardi - Apritasari, Dyah Ayu; , Luluk Ria Rakhma, S.Gz., M.Gizi; , Nur Latifah M, S.Gz, MS (2015)
DEPARTMENT OF DIPLOMA IN NUTRITION FACULTY OF HEALTH SCIENCE MUHAMMADIYAH UNIVERSITY OF SURAKARTA RESEARCH PAPERS ABSTRACT DYAH AYU APRITASARI MAHENDRI. J300120028 RELATIONSHIP BETWEEN CARBOHYDRATE AND CHOLESTEROL INTAKES, AND GLUCOSE LEVELS IN TYPE II DIABETES MELITUS OUTPATIENTS AT Dr. MOEWARDI HOSPITAL OF SURAKARTA. Introduction: Diabetes melitus is a degenerative disease, due to the function and structure of the tissue or organ of the body gradually decrease over time due to age or lifestyle. High blood glucose levels can be affected by consumption of foods high in fat, simple carbohydrates and processed foods along with less physical activity and exercise. Objective: To determine the relationship between the carbohydrates and cholesterol intakes and blood glucose levels in type II diabetes melitus at outpatients at Dr. Moewardi Hospital of Surakarta. Methods: This research was an obsevasional with cross-sectional design. Number of subjects was 55 diabetes melitus type II outpatients at Dr. Moewardi Hospital of Surakarta. Retrieval of subject by sequentional sampling. Intake of carbohydrates and cholesterol data were obtained through recall 24-hours for 4 days. Results: The average consumption of carbohydrate intake was 230,25 ± 57,315 gram. The average cholesterol intake was 210,94 ± 101,28 mg. Corelation between carbohydrate intake and fasting blood sugar showed p value=0,299 and blood sugar 2 hours post-prandial with p value =0,258. Correlation test between intake fasting blood sugar levels showed p value=0,388 and blood sugar 2 hours post-prandial with p value=0,18. Conclusions: There was no relationship between the consumption carbohydrate intake and blood glucose levels of fasting blood sugar and blood sugar 2 hours post-prandial and there was no association between consumption of cholesterol in the blood glucose levels of fasting blood sugar but there was a relationship between cholesterol intake and blood glucose levels blood sugar 2 hours post-prandial . Keywords: carbohydrate intake, cholesterol intake, blood glucose levels. Bibliography: 29 : 1994-2011